Shady practices : agroforestry and gender politics in the Gambia. - Schroeder, Richard A. (California studies in critical human geography ;, 1999)
"Shady Practices is a revealing analysis of the gendered political ecology brought about by conflicting local interests and changing developmental initiatives in a West African village. Between 1975 and 1985, while much of Africa suffered devastating drought conditions, Gambian women farmers succeeded in establishing hundreds of lucrative communal market gardens. In less than a decade, the women's incomes began outstripping their husbands' in many areas, until a shift in development policy away from gender equity and toward environmental concerns threatened to do away with the social and economic gains of the garden boom. Male landholders joined forestry personnel in attempts to displace the gardens and capture women's labor for the irrigation of male-controlled tree crops. This carefully documented microhistory draws on field experience spanning more than two decades and the insights of disciplines ranging from critical human geography to development studies. Schroeder combines the "success story" of the market gardens with a cautionary tale about the aggressive pursuit of natural resource management objectives, however well intentioned. He shows that questions of power and social justice at the community level need to enter the debates of policymakers and specialists in environment and development planning. Shady Practices is a revealing analysis of the gendered political ecology brought about by conflicting local interests and changing developmental initiatives in a West African village. Between 1975 and 1985, while much of Africa suffered devastating drought conditions, Gambian women farmers succeeded in establishing hundreds of lucrative communal market gardens. In less than a decade, the women's incomes began outstripping their husbands' in many areas, until a shift in development policy away from gender equity and toward environmental concerns threatened to do away with the social and economic gains of the garden boom. Male landholders joined forestry personnel in attempts to displace the gardens and capture women's labor for the irrigation of male-controlled tree crops. This carefully documented microhistory draws on field experience spanning more than two decades and the insights of disciplines ranging from critical human geography to development studies. Schroeder combines the "success story" of the market gardens with a cautionary tale about the aggressive pursuit of natural resource management objectives, however well intentioned. He shows that questions of power and social justice at the community level need to enter the debates of policy-makers and specialists in environment and development planning." -- Présentation de l'éditeur.